Mandala Bhakti Wanitatama: memori kolektif pergerakan perempuan dalam terciptanya kesetaraan gender - Jannah, Diah Nadiatul; Cahyani, Devita Eka; Arfaton, Arfaton; Milhani, Yuhanida (JIPSINDO, 2022)
Tujuan penelitian ini adalah mengetahui latar belakang pergerakan laskar perempuan Indonesia untuk menunjang kesetaraan gender dan menghayati nilai-nilai yang terdapat dalam Mandala Bhakti Wanitatama. Metode yang digunakan dalam penelitian ini yaitu kualitatif historis dengan tahapan analisis data yaitu Heuristik, Verifikasi, Interpretasi, dan Historiografi. Penelitian ini dilakukan di Kompleks Mandala Bhakti Wanitatama Yogyakarta. Hasil penelitian ini menunjukkan bahwa Mandala Bhakti Wanitatama dapat memenuhi konsep manusia, ruang, dan waktu dalam sejarah serta dapat merepresentasikan kesetaraan gender yang dilandasi tujuan-tujuan SDGs dan United Nations Development Programme. Mandala Bhakti Wanitatama juga memiliki potensi modal sosial, realitas sosial dan manajerial yang baik dalam proses terciptanya monument lewat kelembagaan.Mandalabhakti Wanitatama: collective memories of women movement for gender equality The purpose of this study was to determine the collective memory of the Indonesian women's movement at the Mandala Bhakti Wanitatama Monument and to reconstruct the values of gender equality contained in the Mandala Bhakti Wanitatama monument. This research is a type of historical qualitative research. This research was conducted at the Mandala Bhakti Wanitatama complex in Yogyakarta for 3 months from July to September 2021. The data collection techniques used were observation, interviews, documentation, and literature studies. The data analysis technique was carried out by heuristics, verification, interpretation, and historiography stages. The results of this study indicate two main things. First, the Mandala Bhakti Wanitatama Monument contains a collective memory of the women's movement that can represent gender equality in line with the goals of the SDGs and the United Nations Development Programme. Second, Mandala Bhakti Wanitatama also has the potential for social capital which consists of the only women's movement museum in Indonesia with various social and managerial realities that are good in the process of creating monuments through institutions.